Implementation of Physical Education Curriculum in Athletics Learning for Sprint Running at Junior High School - Akhmad Sobarna; Sumbara Hambali; Sony Hasmarita; Mohd Shariman Shafie (Institute of Multidisciplinary Research and Community Service, 2026)
The effective implementation of Physical Education (PE) curricula in athletics instruction remains a persistent challenge at the secondary school level, particularly regarding teachers' pedagogical competence and the contextual adaptation of curricula. This study aims to examine the implementation of the PE curriculum in sprint running instruction among eighth-grade students at the Junior High School level. A descriptive quantitative design with a survey approach was employed, involving 94 eighth-grade students selected through total sampling. Data were collected using a validated curriculum implementation observation sheet (validity: r = 0.87; reliability: α = 0.88), a 60-meter sprint performance test, and a learning motivation questionnaire. Data were analyzed using descriptive statistics, paired-samples t-test, and N-gain score calculation. PE curriculum implementation was categorized as